Experimental flexural performance of concrete beams reinforced with an innovative hybrid bars. (1st January 2021) - Said, Mohamed; Shanour, Ali S.; Mustafa, T.S.; Abdel-Kareem, Ahmed H.; Khalil, Mostafa M.
Highlights: Provision of the hybrid bars enhanced the cracking load, ultimate capacity, ductility factor, stiffness, and energy absorption of test beams. The proposed numerical approach is a good tool for modelling concrete beams reinforced with hybrid bars. Nominal flexural strength was performed and assessed with experimental results. Abstract: Twelve half-scale concrete beams were tested to investigate the flexural performance of concrete beams reinforced with locally produced hybrid bars and hybrid schemes. The variables are the reinforcement bar type (hybrid, GFRP, and steel) and the reinforcement ratios (0.85%, 1.26%, 1.70%, 1.8, and 2.13%). The test results showed a significant enhancement in the maximum load-carrying capacity due to increasing the hybrid reinforcement ratio. The capacities were increased by 109% and 167% respectively for hybrid reinforcement ratio of 1.26% and 1.7%. Also, the strain of reinforcing bars exceeds the yield level. Accordingly, using hybrid reinforced bars or hybrid schemes exhibited more ductility for concrete beams. Non-linear finite element analysis (NLFEA) was carried out using ANSYS Software. The analysis adequately reflected the trend of experimental results, the overall average value of the ratio between experimental and NLFEA ultimate capacity is 1.01. Additionally, parametric studies have been performed in order to investigate the effect of concrete compressive strength, hybrid reinforcement ratio and shear-span to depth ratio on the performance of hybrid reinforcement concrete beams. Nominal flexural strength was assessed with the experimental test results and 38 reinforced concrete beams from the literature. The comparison proved that assessment of the nominal flexural strength performs well in predicting the flexural capacity. The average value of the ratio between experimental and nominal flexural strength is 1.011.